DIFFERENTIAL RESPONSE OF SUGARCANE VARIETIES ARIETIES TOWARDS POST-HARVEST STALING LOSSES ALING LOSSES - LENIKA KASHYAP; RAJINDER KUMAR (The Bioscan, 2018)
Postharvest deterioration has become a topic of major concern in recent years due to faulty transport and management issues that effects appropriate cut to crush policy and ultimately sugar recovery. The quality of sugarcane juice at harvest is determined by the concentration of sucrose, which should be high and non sucrose components, which should be low. The present study was thus planned with the objective to access the effect of staling on four early and five mid-late maturing recommended varieties for commercial cultivation in Punjab, in context of the juice quality parameters viz., TSS %, Sucrose %, CCS %, purity %, extraction %, reducing Sugars %, pH and cane weight (Kg). Staling of harvested sugarcane resulted in increase in the level of average TSS of juice from 21.66 % - 26.11 %. Staling also results in gradual decline of average sucrose content (19.13 % - 13.80 %), average CCS % (12.46 % - 5.24 %), average purity % (88.51 % - 53.14 %) with a concomitant rise in the level of average reducing sugars (0.27-5.50%). A drop in mean pH (5.24 - 4.49) of the stale juice was also observed. The study indicated that CoPb 92 from early maturity group and CoPb 93 from mid-late maturity groups are promising candidate varieties possessing tolerance to post harvest deterioration as they retain maximum average sucrose % (17.9, 15.9 %) and CCS % (11.6, 8.8 %) over the staling period, respectively.